LincRNA00494 Suppresses Non-small Cell Lung Cancer Cell Proliferation by Regulating SRCIN1 Expression as a ceRNA - Dong, Jingsi; Li, Bingjie; Lin, Dan; Lu, Dan; Liu, Chang; Lu, Xingbing; Tang, Xiaojun; Li, Lu; Zhu, Daxing; Liu, Jiewei; Qiu, Xiaoming; Tian, Long; et al. (Frontiers in oncology, 2020)
Lung cancer is the most common malignant tumor worldwide. Accumulating results have shown that long non-coding RNAs (lncRNAs) play a key role in tumorigenesis. A total of 163 tumor tissues were collected from non-small cell lung cancer (NSCLC) patients from West China Hospital of Sichuan University. is a novel lncRNA, and its expression and biological effect in NSCLC were reported in this study. NSCLC cell lines were used in this study. is mainly distributed in the cytoplasm. was downregulated in the tumor tissues compared with the adjacent non-tumor tissues. expression was positively correlated with SRCIN1 expression ( = 0.57, < 0.05). Silencing of in the cell lines substantially decreased SRCIN1 expression at the mRNA and protein levels, whereas overexpression of enhanced the SRCIN1 levels. miR-150-3p significantly decreased the luciferase signals of and SRCIN1 reporters. After transfection with miR-150-3p mimics and miR-150-3p inhibitor, overexpression of decreased the proliferation of the H358 (36%) and H1299 (29%) cell lines compared with that of the control cells, as shown by CCK-8 assays, whereas silencing promoted the proliferation of the H358 (47%) and H1299 (35%) cells. Tumor growth from LincRNA00494-overexpressing xenografts was significantly decreased; additionally, LincRNA00494 silencing substantially increased tumor growth compared with that of the control cells. Functional experiments revealed that inhibited NSCLC cell proliferation, which might be related to the suppression of SRCIN1, a tumor suppressor gene, by acting as a decoy for miR-150-3p. The data showed that might have antineoplastic effects during NSCLC tumorigenesis through its role as a ceRNA.